2004
DOI: 10.1029/2004gl020560
|View full text |Cite
|
Sign up to set email alerts
|

Monthly CO surface sources inventory based on the 2000–2001 MOPITT satellite data

Abstract: This paper presents results of the inverse modeling of carbon monoxide surface sources on a monthly and regional basis using the MOPITT (Measurement Of the Pollution In The Troposphere) CO retrievals. The targeted time period is from April 2000 to March 2001. A sequential and time-dependent inversion scheme is implemented to correct an a priori set of monthly mean CO sources. The a posteriori estimates for the total anthropogenic (fossil fuel + biofuel + biomass burning) surface sources of CO in TgCO/yr are 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
177
7
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 13 publications
25
177
7
1
Order By: Relevance
“…Several studies have applied inverse modelling techniques to the optimisation of CO emissions using observations from surface networks (Petron et al, 2004) as well as observations from the MOPITT and IASI satellite instruments. Most of these studies using satellite data have concluded that the a priori anthropogenic emissions of CO might be underestimated as indicated in Fig.…”
Section: Evaluation and Optimisation Of Emissions Using Inverse Modelmentioning
confidence: 99%
“…Several studies have applied inverse modelling techniques to the optimisation of CO emissions using observations from surface networks (Petron et al, 2004) as well as observations from the MOPITT and IASI satellite instruments. Most of these studies using satellite data have concluded that the a priori anthropogenic emissions of CO might be underestimated as indicated in Fig.…”
Section: Evaluation and Optimisation Of Emissions Using Inverse Modelmentioning
confidence: 99%
“…Duncan et al [68] showed a 25% uncertainty remains for fossil fuel CO despite rigorous and extensive bottom-up estimates. The inconsistency of source estimates from the previous inversion analyses shown in Figure 1 also indicates that the uncertainty of each source is at least 20% for anthropogenic, 50% for biomass burning, 100% for biogenic hydrocarbon oxidation, and 15% for CH4 oxidation [14,[16][17][18][19][20][21]. Previous studies also carefully started inversion analyses using weak constraints: 50% of a priori source strength estimates [20,21,68,69,75].…”
Section: Uncertainties In a Priori Source Estimates: S Amentioning
confidence: 98%
“…Carbon monoxide emissions from fossil fuel and biofuel use are taken from [17]. They derived CO source strengths from April 2000 to March 2001 using MOPITT (Measurement of the Pollution in the Troposphere) satellite observations and updated the inventory monthly for 15 regions.…”
Section: Sources and Sinks Of Atmospheric Comentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach (also referred to as inverse modeling of emissions) [86,3,85,51], the emissions are adjusted to best match the model predictions with the observations, within error estimates. The same data assimilation techniques discussed above can encompass emission estimates as well.…”
Section: Incorporating Emissions Into the Analysismentioning
confidence: 99%